2006
DOI: 10.1002/eji.200636156
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of the innate immune responses in wild‐derived inbred strains of mice

Abstract: The vertebrate immune system has evolved to recognize nucleic acids of bacterial and viral origin. Microbial DNA, as well as synthetic oligonucleotides based on these motifs, activates innate immune pathways mediated by the family of Toll‐like receptors (TLR) initiating a cascade of signals in immune cells necessary for responses to pathogens. However, not all of the proteins that participate in TLR‐mediated responses have been identified. In studies described herein, we observed significant variation in innat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…In contrast, wild-derived mice originated mainly from M. m. musculus and M. m. castaneus subspecies are genetically diverse compared to the classical inbred strains. Compared to one another, the genomes of the wild-derived and classical inbred strains show a polymorphism in every 100 to 200 bp (34), suggesting that screening wild-derived mice may uncover other host factors or novel alleles of previously characterized genes that influence L. pneumophila intracellular growth.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, wild-derived mice originated mainly from M. m. musculus and M. m. castaneus subspecies are genetically diverse compared to the classical inbred strains. Compared to one another, the genomes of the wild-derived and classical inbred strains show a polymorphism in every 100 to 200 bp (34), suggesting that screening wild-derived mice may uncover other host factors or novel alleles of previously characterized genes that influence L. pneumophila intracellular growth.…”
Section: Resultsmentioning
confidence: 99%
“…(iii) Third, the same TLR from different strains of the same species might differ in single amino acids, which are essential for the recognition of certain ligands. Indeed, monogenic dominant traits in TLR genes have recently been identified in wild-derived mice strains [50], indicating that studying inbred laboratory strains might fail to capture all the polymorphisms that exist in the mouse species. Such analyses could help to assess genetic predisposition to certain infectious diseases in humans and livestock, and could be used to improve breeding strategies for genetic disease resistance in livestock.…”
Section: Reviewmentioning
confidence: 99%
“…It was of interest to evaluate IMQ dermatitis in MOLF mice, since previous studies have identified MOLF genetic variants impacting Toll-like receptor (TLR) signaling, including alleles associated with Tlr5 [57], Irak1bp1 [56], Irak2 [70], Irak2c [71], and Cyld [72]. These variants appear to alter immune responses of MOLF mice to several stimuli, such as lipoteichoic acid, poly(I:C), lipopolysaccharide, and schistosome infection [18,56,70]. IMQ is a TLR7 agonist and previous work has identified TLR7 expression in a subpopulation of mouse interfollicular epidermal keratinocytes [73].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that MOLF mice exhibit unique responses to TLR agonists, such as lipoteichoic acid, poly(I:C), lipopolysaccharides, cytosine guanine dinucleotide (CpG), and resiquimod [18,56,57]. A set of 101 TLR-associated genes compiled by the Kyoto Encyclopedia of Genes and Genomes (KEGG) [58] was disproportionately elevated by IMQ in all strains, including MOLF males and females (Additional file 12; KEGG pathway mmu04620).…”
Section: Imq Treatment Of Molf Males Induces Tlr Gene Expression But mentioning
confidence: 99%
See 1 more Smart Citation